1995
DOI: 10.1006/dbio.1995.0024
|View full text |Cite
|
Sign up to set email alerts
|

Progression and Recapitulation of the Chondrocyte Differentiation Program: Cartilage Matrix Protein Is a Marker for Cartilage Maturation

Abstract: During endochondral bone formation, chondrocytes in the cartilaginous anlage of long bones progress through a spatially and temporally regulated differentiation program before being replaced by bone. To understand this process, we have characterized the differentiation program and analyzed the relationship between chondrocytes and their extracellular environment in the regulation of the program. Our results indicate that, within an epiphyseal growth plate, the zone of proliferating chondrocytes is not contiguo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
1
3

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 6 publications
4
96
1
3
Order By: Relevance
“…44). The expression of aggrecan mRNA has been also reported to disappear in hypertrophic chondrocytes (1).…”
Section: Expression Of Snail Slug and Type II Collagen Mrnas Duringmentioning
confidence: 97%
See 3 more Smart Citations
“…44). The expression of aggrecan mRNA has been also reported to disappear in hypertrophic chondrocytes (1).…”
Section: Expression Of Snail Slug and Type II Collagen Mrnas Duringmentioning
confidence: 97%
“…During hypertrophic differentiation, the extracellular matrix self-organizes prior to the formation of bone. A switch from collagen type II to collagen type X occurs, and both aggrecan and link protein disappear (1,2). Studies in stable transformants revealed that overexpression of Snail and Slug prevented the expression of major chondrocyte extracellular matrix, collagen type II, and aggrecan when transfected cells were induced to differentiate.…”
Section: Snail-related Transcription Factors Are Repressors Of the Comentioning
confidence: 99%
See 2 more Smart Citations
“…During endochondral ossification, chondrocytes undergo a differentiation process including proliferation, maturation, hypertrophy, and apoptosis (1). Cells from these different stages of differentiation synthesize specific molecules, for example, type X collagen is synthesized specifically by hypertrophic chondrocytes (2,3), whereas cartilage matrix protein (CMP) 1 / matrilin-1, is a marker of prehypertrophic chondrocytes (1).…”
mentioning
confidence: 99%